Mechanisms of Rostellularia procumbens (L.) Nees on treating chronic glomerulonephritis explored by network pharmacology, RNA-seq, and in vitro experiments - Mengfan Wang; Yi Zhou; Qiuyuan Jian; Zhongzhu Ai; Shanshan Zhou (BMC, 2023)
Abstract Background The purpose of this study was to demonstrate the in vitro anti-nephritis activity of Rostellularia procumbens (L.) Nees (R. procumbens) extract and to make a preliminary investigation of its anti-nephritis mechanism. Methods A prediction network was built that describes the relationship between R. procumbens and CGN. Then, the potential targets for R. procumbens against CGN were imported into the DAVID database for Gene Ontology (GO) biological annotation analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. A lipopolysaccharide (LPS)-stimulated rat mesangial cell HBZY-1 model in vitro was used to examine the anti-inflammatory activity of R. procumbens extract. RNA-seq was utilized to investigate differentially expressed genes (DEGs) and enriched signaling pathways between groups. Finally, qPCR was used for the validation analysis of the experimental results. Results The results of network pharmacology showed that R. procumbens exerts its therapeutic effect on CGN through the AGE-RAGE signaling pathway in diabetic complications, PI3K-Akt, IL-17 signaling pathway, and so on. R. procumbens n-butanol extract (J-NE) can effectively relieve inflammation in HBZY-1. The results of KEGG pathway enrichment suggest that J-NE attenuated CGN was associated with the IL-17 signaling pathway, and the results of RNA-seq were consistent with network pharmacology. Targets enriched in the IL-17 signaling pathway, including Chemokine (C-C motif) ligand 7 (CCL7), Lipocalin 2 (LCN2), Chemokine (C-C motif) ligand 2 (CCL2), and Chemokine (C-X-C motif) ligand 1 (CXCL1), have been identified as crucial targets attenuating CGN by J-NE. Conclusion R. procumbens is a promising pharmacological candidate for the treatment of CGN in the present era.